2019
DOI: 10.1080/13691457.2019.1568970
|View full text |Cite
|
Sign up to set email alerts
|

Counselling of people with dementia in legal matters – social and health care professionals’ role

Abstract: This article examines the counselling of people with dementia in legal matters by focusing on the experiences both of people with dementia and of social and health care professionals. The article also assesses the role of social and health care professionals in enabling the fulfilment of the legal security of people with dementia. In Finland, social and health care professionals have a responsibility to inform their clients of their social and legal security options, and therefore need to know the range of leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…In addition, the findings of this study are also in line with the findings of a study conducted by Nikumaa & Leinonen (2019) who found that counsellors' challenges facing older people with dementia were lack of knowledge and skills so that counsellors sometimes failed to provide full information due to their reluctance to provide accurate information. In addition to the basic counselling skills that can be learned while studying at a tertiary institution, there are a number of specific skills that are needed in conducting counselling services with senior citizens.…”
Section: Challenges From the Aspect Of The Counsellorsupporting
confidence: 88%
“…In addition, the findings of this study are also in line with the findings of a study conducted by Nikumaa & Leinonen (2019) who found that counsellors' challenges facing older people with dementia were lack of knowledge and skills so that counsellors sometimes failed to provide full information due to their reluctance to provide accurate information. In addition to the basic counselling skills that can be learned while studying at a tertiary institution, there are a number of specific skills that are needed in conducting counselling services with senior citizens.…”
Section: Challenges From the Aspect Of The Counsellorsupporting
confidence: 88%
“…This suggests the need to build the same care pathway for everyone to ensure their ongoing and equal access to information and services. High-quality guidance and counselling based on multi-disciplinary expertise creates conditions for people to participate in decision-making concerning themselves by providing timely information and support (Heimonen and Mäki-Petäjä-Leinonen, 2018;Nikumaa and Mäki-Petäjä-Leinonen, 2019). Some participants reported that anticipating their future was very important to them.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study illustrate well the situations a person with dementia faces in their daily life— regardless of the pandemic. If they are unable to take care of their affairs, in many cases their loved ones take care of them; either as an informal or formal caretaker, such as a legal guardian [ 44 ]. According to Giebel et al [ 45 ], the task of finding the right services often falls to unpaid carers, which highlights the need for better support both for people with dementia and for their carers to ensure access to services.…”
Section: Discussionmentioning
confidence: 99%